2010
DOI: 10.1116/1.3482343
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of ultralow k-compatible carbon dioxide in situ photoresist ashing processes. I. Process performance and influence on ULK material modification

Abstract: In situ photoresist ͑PR͒ ashing processes are attractive because of the ease of process integration with plasma etching processes. The authors have examined the performance of carbon dioxide ͑CO 2 ͒ as a source gas for in situ PR ashing processes compatible with ultralow k ͑ULK͒ materials and compared it with the results obtained using O 2 . They performed measurements of 193 nm PR ashing rates in a dual frequency capacitively coupled plasma reactor. The damage to porous ULK feature sidewalls was simulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…6 Ming-Shu Kuo et al and Hualiang Shi extensively studied the surface modification of ultralow-k materials by CO 2 plasma and the results are published in their PhD dissertations 7,8 and in several papers. [9][10][11][12][13] They reported that i) CO 2 and O 2 plasma damage to ultralow-k films are comparable ii) there is lower atomic oxygen density in CO 2 discharge than O 2 discharge because of higher activation energy (11.5 eV) required to liberate atomic oxygen from CO 2 than from O 2 molecules (6 eV) -this is why there is supposedly a reduction in damage by CO 2 discharge with respect to O 2 for same operating conditions iii) the ashing rate of CO 2 increases with the addition of Ar at higher pressure (about 100 mTorr) than at lower pressure hence the addition of Ar is beneficial and dependent on pressure. Adding Ar brings about the dilution of the concentration of O 2 atoms that are liberated from CO 2 hence a lower damage to low-k.…”
mentioning
confidence: 99%
“…6 Ming-Shu Kuo et al and Hualiang Shi extensively studied the surface modification of ultralow-k materials by CO 2 plasma and the results are published in their PhD dissertations 7,8 and in several papers. [9][10][11][12][13] They reported that i) CO 2 and O 2 plasma damage to ultralow-k films are comparable ii) there is lower atomic oxygen density in CO 2 discharge than O 2 discharge because of higher activation energy (11.5 eV) required to liberate atomic oxygen from CO 2 than from O 2 molecules (6 eV) -this is why there is supposedly a reduction in damage by CO 2 discharge with respect to O 2 for same operating conditions iii) the ashing rate of CO 2 increases with the addition of Ar at higher pressure (about 100 mTorr) than at lower pressure hence the addition of Ar is beneficial and dependent on pressure. Adding Ar brings about the dilution of the concentration of O 2 atoms that are liberated from CO 2 hence a lower damage to low-k.…”
mentioning
confidence: 99%
“…Acceptable resist etch rates (100 nm/min) can be achieved by using a high temperature (260°C) downstream H 2 plasma. The CO-or CO 2 -based resist strip approaches are generally run in RIE tools [55,65,66]. The downstream H 2 plasma only reacts with H in the low-k film, in a replacement reaction, without altering the stoichiometry of the film [64].…”
Section: Dielectric Patterningmentioning
confidence: 99%
“…It has been reported that residues are left after a downstream H 2 plasma strip, which must be removed with a wet clean [63]. Argon is often added to the strip chemistry and a bias is applied to the wafer to enable a high removal rate of resist [66]. Hence, there is no change in the film thickness or dielectric constant.…”
Section: Dielectric Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…Major problems are delamination caused by chemical mechanical planarization and drastic change in the dielectric due to pore-induced damage occurring in the wet cleaning and ashing processes. Since porous SiOCH occupies a lot of space in a film, it is fragile and readily absorbs any solutions or gases [1][2][3][4][5]. Moreover, Cu atoms easily diffuse into the SiOCH through pores.…”
Section: Introductionmentioning
confidence: 99%